Image quality in chest tomography employing three different equipment technologies - Kátia Pedrosa Silva; Maria do Socorro Nogueira (Brazilian Journal of Radiation Sciences, 2021)
Computed tomography represents the largest portion of the population´s exposure to ionizing radiation related to medical imaging. This article aims to assess the quality of the images through the analysis of radiologists in routine chest protocols, performed at one hospital and two diagnostic imaging clinics, and employing three equipment with different technologies. A total of 1,088 criteria were analyzed with the three imaging techniques, and the average percentage of the observed structures were 95, 99 and 99% for each service. There was an excellent correlation between observers and even an absolute agreement in some cases for the most modern technologies. The three studied devices provided acceptable dose values and images with a quality close to 100%, reducing the exposure and improving the radiological protection of patients.